Forensic Linguistics Function in Evidentiary - Bila, Alona (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2024)
Linguistic expertise is a specialized linguistic study of textual materials and other language objects to clarify issues that may have legal implications. Searching for answers to questions that arise during investigation and court proceedings usually requires special linguistic knowledge. Research in foren-sic linguistics is conducted in order to determine the time and place of docu-ment creation, the text’s scribe and author, the use of force against the scribe in the course of creating a document, and overall to establish whether the document is fake or authentic. Statistical methods of text analysis are widely used in forensic linguistics.
Keywords: forensic linguistics; expert; evidentiary; texts of oral and written speech; verbal; letter; phonetic notations; combined notations